Association between Variations in Body Mass Index and Cognitive Function in Older Korean Adults - Eun Mi Bae; Sang Min Park (Journal of Obesity & Metabolic Syndrome, 2021)
Background : Although several studies have assessed obesity and cognitive impairment, most of these studies focus on body mass index (BMI) and cognitive impairment. Therefore to better understand the importance of weight maintenance with aging, this study investigated the relationship between variations in weight and cognitive impairment using the Korean version of the Mini-Mental State Examination (K-MMSE) in individuals aged 45 years or older in Korea. Methods : Data on 3,477 adults with normal cognitive function (K-MMSE ≥24) at baseline were acquired from the Korean Longitudinal Study of Aging (KLoSA) 2006-2016. The association between weight variability and risk of cognitive impairment was assessed using multiple logistic regression models. We also assessed weight variability and change in cognitive function over the 6-year follow-up using multiple linear regression. Results : Overall, higher variations in BMI were associated with cognitive impairment. Patients in the quintile with the highest variation (Q5) in BMI (mean of BMI changes, 2.69) showed the greatest degree of cognitive impairments (adjusted odds ratio, 1.52; 95% confidence interval [CI], 1.08-2.14; P for trend=0.016). Furthermore, a higher frequency in the number of times (3 times) the patient’s body weight changed was associated with a lower cognitive function (adjusted odds ratio, 3.42; 95% CI, 1.67-7.03; P for trend<0.001). Conclusion : In this nationally representative study, weight variability was associated with a higher risk of cognitive decline during mid- and late-life stages.